Dietary Risk Assessment and Ranking of Multipesticides in Dendrobium officinale - Meng-Ying Gu; Peng-Si Wang; Shang-Mei Shi; Jian Xue (Journal of Food Quality)
The presence of pesticide residues in Dendrobium officinale (D. officinale), a commonly used herbal medicine, has attracted much attention in recent years. Therefore, this study presents the levels of 141 pesticide residues in forty D. officinale samples, which were measured by high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). And we used a deterministic estimate model to assess chronic and acute dietary exposure risk, as well as the cumulative risks for adults, children, and specific groups of consumers. Furthermore, the residual risk of individual pesticides was sorted by adapting the matrix-ranking scheme. In 92.5% of the samples, 43 pesticides were detected, of which difenoconazole had the highest detection frequency. Multiple residues were detected in 85.0% of the samples, and one sample contained even up to 17 pesticides. The chronic hazard quotient (HQc) and the acute hazard quotient (HQa) were far below 100%, and both cumulative chronic and acute hazard indices (HI) did not exceed 100%. The risk scoring scheme showed that four pesticides were considered to pose a comparatively potential high risk, including difenoconazole, carbofuran, fipronil, and emamectin benzoate. The results indicated that the occurrence of pesticide residues in D. officinale could not pose a serious health problem to the public.